THE EFFECT OF COMMUNITY PARTICIPATION ON THE PREVENTION OF DENGUE FEVER - Ika Syani Putri Lubis; Rosari Inriani S (Yayasan Nuraini Ibrahim Mandiri, 2026)
Dengue Hemorrhagic Fever is one of the most common health problems in the community that causes various health problems. This study aims to determine the influence of community participation on the implementation of Dengue Fever prevention programs at the Tanjung Morawa Community Health Center, Deli Serdang Regency. This study is a quantitative analytical survey study with a cross-sectional design. The sample used was 270 people. Data analysis used univariate analysis, bivariate analysis and multivariate analysis. The results of statistical tests using chi-square analysis showed no relationship between age (p = 0.851), education level (p = 0.688), occupation (p = 0.336), attitude (p = 0.167), stakeholder role (p = 1.000) with community participation in the implementation of DHF prevention, while there was a relationship between gender (p = 0.019), knowledge (p = 0.002) and information sources (p = <0.001) with community participation in the implementation of DHF prevention. The conclusion of this study is that there is a relationship between gender and information sources and community participation in implementing dengue prevention.